(untitled) (Bulletin KNOB, 2015)
Amsterdam experienced the greatest upturn in its economic fortunes in the sixteenth and seventeenth centuries. This went hand in hand with brisk building activity throughout the city. As part of studies into construction history, 679 samples of wood were subjected to dendrochronological examination. Since Amsterdam very swiftly exhausted local wood supplies, the city had to rely on importing wood to cover its immense needs. On the basis of the dendrochronologically defined samples, this article not only presents the individual datings, but also attempts to analyze the timber trade in the city in the context of the overall political situation. Since the countries bordering on the Baltic Sea formed an unstable economic region at this time owing to the Nordic Wars, two other main zones were tapped. First, a lot of timber was procured from south Norway and western Sweden, enabling Danish customs duties to be avoided that would otherwise have been levied on goods moving from the Baltic. The preference was for high-grade fine-ringed oak and pine. Second, wood was purchased from the region along the Elbe and Havel rivers, whereby the timber was traded through Hamburg. Prussia made use of canals that ran deep into the central reaches of the Oder River and beyond as sources of wood. The specialty from this area were long trunks of pinewood. These trade relations survived, along with the associated rafting on inland waterways, into the most recent past. Despite its massive scale, timber trade down the Rhine only played a minor role for Amsterdam. Evidently the timber in question tended to be sold more in the western Dutch provinces and in long-distance trade from the west.